Six-months clinical and intracoronary imaging follow-up after reverse T and protrusion or double-kissing and crush stenting for the treatment of complex left main bifurcation lesions - Abouelnour, Amr EI; Olschewski, Maximilian; Makmur, Giulio; Ullrich, Helen; Knorr, Maike; Ahoopai, Majid; Münzel, Thomas; Gori, Tommaso (Frontiers in Cardiovascular Medicine, 2023)
Background: There is a debate regarding the best stent strategy for unprotected distal left main (LM) bifurcation disease. Among two-stent techniques, double-kissing and crush (DKC) is favored in current guidelines but is complex and requires expertise. Reverse T and Protrusion (rTAP) was shown to be a comparable strategy regarding short-term efficacy and safety, but with reduced procedural complexity. Aim: To compare rTAP versus DKC by optical coherence tomography (OCT) on the intermediate term. Methods: 52 consecutive patients with complex unprotected LM stenoses (Medina 0,1,1 or 1,1,1) were randomized to either DKC or rTAP and followed-up for a median of 189[180-263] days for clinical and OCT outcomes. Results: At follow-up OCT showed similar change in the side branch (SB) ostial area (primary endpoint). The confluence polygon showed a higher percentage of malapposed stent struts in the rTAP group that did not reach statistical significance (rTAP: 9.7[4.4-18.3] % vs DKC: 3[0.07-10.9] %; p=0.064). It also showed a trend towards larger neointimal area relative to the stent area (DKC: 8.8 [6.9 to 13.4] % vs rTAP: 6.5 [3.9 to 8.9] %; p=0.07), and smaller luminal area (DKC: 9.54[8.09-11.07] mm2 vs rTAP: 11.21[9.53-12.42] mm²; p=0.09) in the DKC group. The minimum luminal area in the parent vessel distal to the bifurcation was significantly smaller in the DKC group (DKC: 4.64 [3.64 to 5.34] mm² vs rTAP: 6.76 [5.20 to 7.29] mm²; p=0.03). This segment also showed a trend for smaller stent areas (p=0.05 to 0.09), and a bigger neointimal area relative to the stent area (DKC: 8.94 [5.43 to 10.5] vs rTAP: 4.75 [0.08 to 8.5]; p=0.06) in the DKC patients. The incidence of clinical events was comparably low in both groups. Conclusion: At 6-months, OCT showed a similar change in the SB ostial area (primary endpoint) in rTAP compared to DKC. There was also a trend for smaller luminal areas in the confluence polygon and the distal parent vessel, and a larger neointimal area relative to the stent area, in DKC, along with a tendency for more malapposed stent struts in rTAP. Trial registration: NCT03714750, registered on October 22nd, 2018.